Preparation method of interface modification layer of garnet solid-state electrolyte and solid-state lithium metal battery

CN122931098APending Publication Date: 2026-10-16ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611066990.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]然而,LLZO基固态电池的商业化应用仍面临两大关键挑战:

Benefits of technology

1.原位形成具有界面能分化特征的梯度界面层:本发明采用磁控溅射FTO层与熔融锂原位反应,由于氟与锂的反应活性远高于锡与锂的反应,首先在表层生成致密的LiF层,同时Sn被还原并与锂形成Li-Sn合金(主要为Li17Sn4相),并伴有少量Li2O。X射线光电子能谱(XPS)深度刻蚀和飞行时间二次离子质谱(TOF-SIMS)证实了表层LiF富集、内层Li2O、Li-Sn合金富集的梯度结构。LiF|Li为高界面能(疏锂),Li17Sn4|Li为低界面能(亲锂),伴随物理结构上的梯度分布,同时这种热力学上高界面能与低界面能的共存构成了显著的界面能落差,从而构筑起具有界面能分化特征的界面环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931098A_ABST
    Figure CN122931098A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an interface modification layer between lithium metal and a garnet solid-state electrolyte and a solid-state lithium metal battery, and comprises the following steps: S1, preparing a tantalum-doped garnet solid-state electrolyte; S2, depositing an FTO layer on the surface of the tantalum-doped garnet solid-state electrolyte by using a plasma magnetron sputtering method; and S3, carrying out in-situ reaction of the tantalum-doped garnet solid-state electrolyte with the FTO layer obtained in the step S2 and molten lithium metal, so as to obtain an interface modification layer between the tantalum-doped garnet solid-state electrolyte and the lithium metal. The preparation method of the solid-state lithium metal battery comprises a positive electrode, a lithium metal negative electrode and a tantalum-doped garnet solid-state electrolyte between the positive electrode and the lithium metal negative electrode, and the tantalum-doped garnet solid-state electrolyte is provided with the interface modification layer prepared by the above method between the tantalum-doped garnet solid-state electrolyte and the lithium metal negative electrode, so as to solve the technical problems of high interface impedance between the tantalum-doped garnet solid-state electrolyte and the lithium metal and easy penetration of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to a method for preparing an interface modification layer of a garnet solid electrolyte and a solid lithium metal battery. Background Technology

[0002] Against the backdrop of the global energy structure transitioning towards sustainability, lithium metal batteries (LMBs) are considered a core candidate for next-generation high-energy-density energy storage systems. However, traditional LMBs using liquid organic electrolytes pose serious safety hazards. When lithium dendrites grow uncontrollably and penetrate the electrolyte, they can trigger an internal short circuit, leading to violent spontaneous discharge and a series of exothermic reactions. These processes rapidly release a large amount of heat, which may ignite the flammable organic liquid electrolyte within the battery, ultimately inducing severe thermal runaway and posing a potential safety hazard.

[0003] Correspondingly, the intrinsic non-flammable properties of solid-state electrolytes (SSEs) can fundamentally improve battery safety; and compared to traditional graphite anodes, they only have a capacity of 372 mAh g. -1 The theoretical specific capacity of lithium anode is as high as 3860 mAh g. -1 Therefore, solid-state lithium metal batteries are considered one of the most promising next-generation energy storage devices. SSEs include solid polymer electrolytes (SPEs), inorganic solid electrolytes (ISEs), and composite solid electrolytes (CSEs). SPEs are considered an important candidate material to replace traditional liquid electrolytes due to their excellent safety performance. However, their ionic conductivity at room temperature is relatively low, typically ranging from 10⁻⁷ to 10⁻⁶. -5 S cm -1 The low efficiency of SPEs severely limits their application prospects in high-performance batteries. Furthermore, SPEs have a relatively narrow electrochemical stability window, are prone to decomposition at high voltages, and suffer from insufficient mechanical strength, making it difficult to effectively suppress lithium dendrite growth and penetration. In contrast, ISEs, such as sulfide, halide, and garnet materials, combine high ionic conductivity with good thermal stability, achieving a better balance between safety and performance. However, sulfide and halide electrolytes still face certain challenges in practical applications, mainly due to their sensitivity to environmental humidity and potential adverse interfacial reactions with lithium metal anodes and high-voltage cathodes, affecting the long-term stable operation of the battery. In contrast, LLZO (tantalum-doped garnet solid electrolyte) possesses high strength and hardness, a wide electrochemical stability window greater than 5V, relatively high ionic conductivity at room temperature, good chemical stability, and excellent air stability. Therefore, LLZO is considered one of the key materials most likely to realize the practical application of solid-state batteries.

[0004] However, the commercial application of LLZO-based solid-state batteries still faces two key challenges: 1. Severe interface problems: The contact between LLZO and the lithium metal anode is solid-solid, with poor interfacial wettability, resulting in extremely high interfacial impedance. At the same time, LLZO is sensitive to water and CO2 in the air, and a Li2CO3 / LiOH insulating layer is easily formed on the surface, which further deteriorates interfacial ion transport and induces uneven lithium deposition.

[0005] 2. Lithium dendrite penetration problem: During battery cycling, lithium dendrites can nucleate and grow along defects such as grain boundaries, pores and cracks of LLZO, eventually penetrating the electrolyte and causing internal short circuits in the battery, leading to safety hazards and battery failure.

[0006] This invention, for the first time, achieves energy-selective regulation of lithium nucleation, growth, and stripping behavior by constructing an interfacial environment with interfacial energy differentiation characteristics. This guides lithium to exhibit a sparse nucleation and lateral spreading growth pattern, resulting in a dense and ordered deposition layer. Simultaneously, it suppresses the formation of interfacial voids during stripping from the source, thereby effectively inhibiting dendrite growth at the thermodynamic level. Summary of the Invention This application aims to solve the technical challenges of high interfacial impedance and easy penetration of lithium dendrites between tantalum-doped garnet solid electrolytes and lithium metal. A layer of FTO (fluorine-doped tin oxide) film is plasma-magnetically sputtered onto the surface of the tantalum-doped garnet solid electrolyte, followed by in-situ reaction with molten lithium. This spontaneously forms a gradient interface layer with significant interfacial energy differentiation: the outer layer is a high-interfacial-energy (lithophobic) region rich in LiF, while the inner layer is a low-interfacial-energy (lithophile) region rich in Li-Sn alloy. This structure guides lithium ions to preferentially nucleate at the lithiophilic sites in the inner layer, while the lithiophobic region of the outer layer inhibits random nucleation and drives lateral lithium expansion, ultimately forming a dendrite-free, flat lithium deposition layer.

[0007] This application provides a method for preparing an interface modification layer between lithium metal and a garnet solid electrolyte, characterized by the following steps: S1 preparing a tantalum-doped garnet solid electrolyte; S2 depositing an FTO layer on the surface of the tantalum-doped garnet solid electrolyte using a plasma magnetron sputtering method; S3 reacting the tantalum-doped garnet solid electrolyte with the FTO layer obtained in step S2 with molten lithium metal in situ to obtain an interface modification layer located between the tantalum-doped garnet solid electrolyte and lithium metal. This interface modification layer has a gradient structure with LiF enriched on the surface, Li2O enriched in the inner layer, and Li-Sn alloy enriched. The interface energy between LiF and Li is higher than that between Li2O and Li-Sn alloy and Li, forming a significant thermodynamic interface energy difference, thereby jointly constructing an interface environment with clear energy differentiation characteristics.

[0008] Preferably, in step S2, the plasma magnetron sputtering uses an FTO target with a SnO2 to SnF2 mass ratio of (90-98):(2-10), an argon sputtering atmosphere, a sputtering pressure of 0.25-2 Pa, and a sputtering time of 30-90 s.

[0009] Preferably, the sputtering pressure is 1.5 Pa and the sputtering time is 60 s.

[0010] Preferably, the in-situ reaction in step S3 is specifically carried out by heating to 200-400°C under an inert atmosphere for a reaction time of 0.5-2 min.

[0011] Preferably, the in-situ reaction in step S3 is specifically carried out by heating to 300°C under an inert atmosphere for 1 minute.

[0012] Preferably, the preparation of the tantalum-doped garnet solid electrolyte in step 1 includes: S1.1 mixing lithium source, lanthanum source, zirconium source and tantalum source in a molar ratio of 6.5:3:1.5:0.5, and adding an excess of 15wt% lithium source, ball milling, drying and sieving; S1.2 calcining at 950℃ for 6h to obtain precursor powder; S1.3 pressing the precursor powder into tablets and sintering at 1280~1320℃ for 10~60min.

[0013] Preferably, the interface modification layer includes LiF and Li 17 Sn4.

[0014] Preferably, the morphological characteristics of the interface modification layer observed by in-situ atomic force microscopy are characterized by sparse nucleation of lithium deposition, lateral growth, and the final formation of a flat and smooth morphology.

[0015] Another subject of this application is a solid-state lithium metal battery, comprising a positive electrode, a lithium metal negative electrode, and a tantalum-doped garnet solid electrolyte located between the two, wherein the tantalum-doped garnet solid electrolyte and the lithium metal negative electrode have an interface modification layer prepared by the above method.

[0016] Compared with the prior art, the present invention has the following advantages: 1. In-situ formation of a gradient interface layer with interfacial energy differentiation characteristics: This invention employs magnetron sputtering of an FTO layer and in-situ reaction with molten lithium. Since the reactivity of fluorine with lithium is much higher than that of tin with lithium, a dense LiF layer is first formed on the surface. Simultaneously, Sn is reduced and forms a Li-Sn alloy with lithium (mainly Li). 17 Sn4 phase), accompanied by a small amount of Li2O. X-ray photoelectron spectroscopy (XPS) depth etching and time-of-flight secondary ion mass spectrometry (TOF-SIMS) confirmed a gradient structure enriched in surface LiF, inner Li2O, and Li-Sn alloy. LiF|Li has a high interface energy (lithophobic), and Li...17 Sn4|Li has low interfacial energy (lithophile) and is accompanied by a gradient distribution in its physical structure. At the same time, the coexistence of high and low interfacial energy in thermodynamics constitutes a significant interfacial energy gap, thus creating an interfacial environment with interfacial energy differentiation characteristics.

[0017] 2. Interfacial energy differentiation regulates lithium deposition morphology, achieving dendrite-free deposition: Compared with the SnO2 control system that only generates low-interfacial-energy Li2O and Li-Sn alloys (without LiF), the FTO-derived interface of this invention exhibits completely different behavior during lithium deposition. In-situ atomic force microscopy (AFM) observations show that during the nucleation stage, lithium preferentially nucleates in the low-interfacial-energy Li2O and Li-Sn alloy regions (corresponding positions in the inner layer). Due to the significant restriction of effective nucleation sites by the LiF region, the nucleation density is low, and the initial lithium nuclei are sparse and relatively large (average diameter of approximately 1.2 μm). During the growth stage, the high-interfacial-energy LiF surface inhibits the formation of new nuclei, and subsequent lithium ions can only deposit on existing nuclei, preferentially expanding laterally driven by minimizing interfacial energy to cover the LiF surface. Quantitative roughness evolution shows that it gradually increases from an initial 40 nm to 90 nm (nucleus growth), then decreases to 50 nm (lateral expansion), sharply increases to 150 nm at the moment when the nuclei are about to connect (local material rearrangement), and then sharply decreases to 40 nm (smooth flat layer) after complete connection. This ultimately results in a large, flat, dendrite-free lithium deposition layer. In contrast, the comparative example (SnO2, without LiF) exhibits high nucleation density, small nuclei, continuous new nuclei formation, vertical growth, and a continuously increasing roughness.

[0018] 3. Significantly reduced interfacial impedance and improved wettability: Unmodified LLZTO has a contact angle greater than 120° with molten lithium, and its interfacial impedance is as high as hundreds of Ω·cm². After the FTO layer of this invention reacts in situ with molten lithium, the Li-Sn alloy lithiophilic component in the interfacial layer causes the molten lithium to spread instantly, reducing the contact angle to near 0°. The interfacial impedance (Li|LLZTO) decreases from the original unmodified >1000 Ω·cm² to 8.5 Ω·cm² (Example 2, sputtering 60s), a reduction of more than two orders of magnitude. In-situ electrochemical impedance spectroscopy (EIS) and relaxation time distribution (DRT) analysis further show that the interfacial modification layer significantly enhances the lithium-ion diffusion kinetics in the low-frequency region, increasing the lithium-ion diffusion coefficient by an order of magnitude.

[0019] 4. Excellent electrochemical cycling stability: When the interface-modified layer prepared in this invention is applied to a Li|LLZTO|Li symmetric cell, it exhibits excellent electrochemical cycling stability at a current density of 0.2 mA cm⁻¹. - ², Deposition capacity 0.2 mAh cm⁻¹ -Under certain conditions, it can be stably cycled for over 10,000 hours, with voltage polarization remaining stable (<30 mV). Critical current density (CCD) testing shows that the interface layer of this invention enables the CCD to operate at 0.2 mA cm⁻¹ of bare LLZTO. - ² Increased to 1.6 mA cm⁻¹ - ². The all-solid-state battery assembled with LFP cathode retains a capacity of over 96.89% after 1000 cycles at 1 C rate, which is far superior to the unmodified battery (which short-circuit in less than 50 cycles).

[0020] 5. Simple process and strong versatility: This invention adopts a mature magnetron sputtering process, which can rapidly deposit FTO layers at room temperature (30-90 seconds) without high-temperature annealing and is compatible with existing solid-state electrolyte production lines. The in-situ reaction only requires brief contact (1 minute) between the FTO / LLZTO sheet and molten lithium, making the operation simple and easy to scale up. This strategy is not only applicable to LLZTO, but can also be extended to other garnet components (such as LLZO, LLZNO, etc.) and other solid-state electrolyte systems.

[0021] The core of this invention lies in utilizing the high reactivity of fluorine to induce spatial gradient interface and thermodynamic interface energy differentiation, rather than simply reducing contact resistance. Comparative experiments have demonstrated that using only SnO2 (fluorine-free) cannot form a high-interface-energy LiF surface layer. The interface products are uniform, resulting in a uniform interface energy across the region. Consequently, it is impossible to achieve sparse lithium nucleation and lateral growth through interface energy differentiation, ultimately leading to dendrite growth. The FTO layer and its plasma-assisted sputtering method described in this invention are key to achieving superior performance. Attached Figure Description

[0022] Figure 1 The intrinsic ionic conductivity of the tantalum-doped garnet solid electrolyte obtained in Example 1 of this invention was tested. Figure 2 This is a cross-sectional scanning electron microscope image of the tantalum-doped garnet solid electrolyte obtained in Example 1 of the present invention; Figure 3 The diagram shows the evolution of the lithium deposition morphology of the Li|FTO-LLZTO interface obtained in Example 1 and the Li|SnO2-LLZTO interface obtained in Comparative Example 2 under in-situ AFM observation. Figure 4 The AC impedance spectra of symmetrical cells obtained by the methods described in Embodiment 1, Comparative Example 1, and Comparative Example 2 of this invention; Figure 5 The graph shows the critical current density test results of the symmetrical cells prepared by the methods described in Embodiment 1, Comparative Example 1 and Comparative Example 2 of the present invention in constant current mode at 25°C. Figure 6The symmetrical cells prepared by the methods described in Embodiment 1, Comparative Example 1, and Comparative Example 2 of this invention have an efficiency of 0.2 mA / cm². 2 Stability cyclic test results at current density; Figure 7 The image shows the SEM image of the interface layer of the FTO-LLZTO electrolyte sheet in Embodiment 2 of the present invention and the corresponding EDS elemental distribution map, including Ta, Zr, La, F and Sn. Figure 8 EIS Nyquist plots of the Li|FTO-LLZTO-FTO|LFP, Li|SnO2-LLZTO-SnO2|LFP and Li|LLZTO|LFP full cells obtained in Example 2, Comparative Example 1 and Comparative Example 2 of this invention; Figure 9 The cycling performance of the Li|FTO-LLZTO|LFP, Li|SnO2-LLZTO|LFP and Li|LLZTO|LFP full cells obtained in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention at 1C. Detailed Implementation

[0023] First, those skilled in the art should understand that these embodiments are merely used to explain the technical principles of the embodiments of this application and are not intended to limit the scope of protection of the embodiments of this application. Those skilled in the art can make adjustments as needed to adapt to specific application scenarios.

[0024] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0025] Example 1 A method for modifying the interface between lithium metal and a garnet-type solid electrolyte includes the following steps: Step 1: Preparation of tantalum-doped garnet solid electrolyte (LLZTO) (1) Raw material pretreatment: La2O3 powder was heat-treated at 900℃ for 12 hours to remove adsorbed moisture and CO2. LiOH·H2O (AR), La2O3 (99.99%), ZrO2 (AR), and Ta2O5 (99.99%) were accurately weighed in a molar ratio of 6.5:3:1.5:0.5, and an additional 15wt% of LiOH·H2O was added to compensate for lithium volatilization during the high-temperature sintering process.

[0026] (2) Ball milling: Place the weighed raw material in a zirconia ball mill jar, add isopropanol as the grinding medium, and use yttrium-stabilized zirconia (YSZ) balls to ball mill at 300 rpm for 8 hours to ensure that the raw material is fully and evenly mixed.

[0027] (3) Drying and calcination: The ball-milled slurry was vacuum dried at 80 °C for 12 hours and passed through a 200-mesh sieve. The sieved powder was placed in an alumina crucible and heated to 950 °C in a muffle furnace at a heating rate of 5 °C / min. The temperature was held for 6 hours for calcination. After natural cooling, the precursor powder was obtained.

[0028] (4) Secondary ball milling and sieving: The precursor powder is ball milled again under the same conditions for 6 hours, dried and then sieved through a 200-mesh sieve to obtain a refined precursor powder.

[0029] (5) Pressing and sintering: Take 0.5g of refined precursor powder and press it into a disc with a diameter of 12.5mm and a thickness of about 1mm under a pressure of 20MPa. Place the blank in a magnesium oxide crucible and cover it with powder of the same composition to prevent lithium volatilization. Sinter it in a box furnace at a temperature of 5℃ / min to 1320℃ and hold for 10 minutes. Cool it to room temperature with the furnace to obtain a dense LLZTO ceramic disc. Polish the surface with sandpaper and ultrasonically clean it with isopropanol for 10 minutes. Dry it to obtain tantalum-doped garnet solid electrolyte, denoted as LLZTO.

[0030] Step 2: Magnetron sputtering deposition of FTO An RF magnetron sputtering system was used, with a 99.99% pure FTO ceramic target (the mass ratio of SnO2 to SnF2 in the FTO target was 90:10). The LLZTO sheet prepared in step 1 was fixed on the sample stage inside the sputtering chamber, and the base vacuum was evacuated to 3 × 10⁻⁶. -4 Pa. High-purity argon (99.999%) was used as the sputtering atmosphere, the working pressure was adjusted to 1.5 Pa, the RF power was set to 100 W, and the sputtering time was 60 seconds (room temperature, no heating required). After sputtering, the sample was allowed to cool naturally and then removed, resulting in LLZTO with a surface-deposited FTO layer (denoted as FTO-LLZTO).

[0031] Step 3: In-situ formation of the interface decoration layer FTO-LLZTO was placed on a heating stage in an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm) and heated to 300°C. A small piece of freshly scraped, shiny lithium metal was melted and applied to the surface of the FTO-LLZTO, maintaining contact for 1 minute to allow the surface layer to fully react with the molten lithium. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. The contact layer between the molten lithium and the tantalum-doped garnet solid electrolyte is the interface modification layer, with the molten lithium serving as the battery's negative electrode.

[0032] Example 2 A method for preparing a solid-state lithium metal battery includes the following steps: Step 1: Preparation of tantalum-doped garnet solid electrolyte (LLZTO) Same as Example 1. Step 2: Magnetron sputtering deposition of FTO layer Same as Example 1.

[0033] Step 3: In-situ formation of the interface decoration layer Same as Example 1.

[0034] Step 4: Assembly of the full battery The active material, conductive carbon black, and polyvinylidene fluoride (PVDF) were dispersed in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 80:10:10. The mixture was stirred to obtain a uniform slurry, which was then coated onto aluminum foil and dried under vacuum at 60 °C for 24 h to obtain the positive electrode of the battery, denoted as LEP.

[0035] The side of the tantalum-doped garnet solid electrolyte without magnetron sputtering deposited FTO layer is brought into contact with the positive electrode. 5 μL of ionic liquid is dropped at the interface between the tantalum-doped garnet solid electrolyte and the positive electrode, and the battery is encapsulated in an argon-filled glove box to obtain a solid lithium metal battery, denoted as Li|FTO-LLZTO|LFP.

[0036] Comparative Example 1 The surface of the tantalum-doped garnet solid electrolyte was not modified with an interface.

[0037] A method for modifying the interface between lithium metal and garnet-type solid electrolyte includes the following steps: Step 1: Preparation of tantalum-doped garnet solid electrolyte (LLZTO) Same as step 1 in Example 1.

[0038] Step 2: In-situ formation of the interface modification layer Replace FTO-LLZTO with LLZTO, and the rest is the same as step 3 in Example 1.

[0039] Comparative Example 2 Surface sputtering of SnO2 on tantalum-doped garnet solid electrolyte A method for modifying the interface between lithium metal and garnet-type solid electrolyte includes the following steps: Step 1: Preparation of tantalum-doped garnet solid electrolyte (LLZTO) Same as step 1 in Example 1.

[0040] Step 2: Magnetron sputtering deposition of SnO2 Replace FTO with SnO2 to obtain LLZTO with SnO2 deposited on the surface (denoted as SnO2-LLZTO). The rest is the same as step 2 in Example 1.

[0041] Step 3 Replace FTO-LLZTO with SnO2-LLZTO, and the rest is the same as step 3 in Example 1.

[0042] Material characterization (1) Intrinsic ionic conductivity test of tantalum-doped garnet solid electrolyte (LLZTO): Silver was sputtered on both sides of the LLZTO sheet prepared in Example 1 as blocking electrodes, and AC impedance was tested at 30°C with a frequency range of 1 Hz to 1 MHz and an amplitude of 10 mV. The test results are as follows: Figure 1 As shown, the ionic conductivity of LLZTO, calculated through fitting, is 6.66 × 10⁻⁶. -4 S / cm.

[0043] (2) SEM observation: The LLZTO cross-section was observed using a scanning electron microscope, such as... Figure 2 As shown, the ceramic sheet is dense, without through-pores, with closely packed particles and clear grain boundaries.

[0044] (3) In-situ AFM observation: In-situ AFM testing was performed on the samples of Example 1 and Comparative Example 2, such as... Figure 3 As shown, the evolution of lithium deposition morphology between FTO and SnO2 surface interface layers within a time window from 0 to 1980 s was compared and analyzed, revealing the key regulatory mechanism of interface energy differentiation on lithium nucleation and growth behavior in the fluorine-doped system: the high interface energy (lithophobic) between the surface LiF and lithium inhibits the random formation of new nuclei; the low interface energy (lithophilic) between the inner Li-Sn alloy and lithium provides preferential nucleation sites. The two work synergistically to guide sparse lithium nucleation at limited sites and drive subsequent lateral lithium growth to cover the high-energy surface, ultimately forming a flat, dendrite-free lithium deposition layer. In contrast, the tin oxide (SnO2) sample only generates Li-Sn alloy and Li2O after reacting with molten lithium, lacking a LiF surface layer. Its entire surface is a low interface energy (lithophilic) region with dense nucleation sites, resulting in lithium ions dispersed on a large number of nuclei, forming high-density, small-sized initial nuclei; during growth, new nuclei continuously form, lithium grows mainly vertically, surface roughness continuously increases, easily evolving into dendritic morphology, and exhibiting poor cycle stability. This comparison illustrates that the fluorine-free system cannot construct interfacial energy differentiation, and therefore cannot achieve sparse nucleation and lateral growth.

[0045] Performance testing Preparation of symmetric cells The two sides of the tantalum-doped garnet solid electrolyte were treated with the interface methods described in Examples 1, 1, and 2 to form sandwich structures of Li|FTO-LLZTO-FTO|Li (Example 1), Li|LLZTO|Li (Comparative Example 1), and Li|SnO2-LLZTO-SnO2|Li (Comparative Example 2). The sides of the structure were then sanded to remove excess lithium metal remaining from the friction process. Finally, the assembled sandwich structure was placed in a CR2032 coin cell casing, and a stacking pressure of 300 psi was applied to obtain a symmetrical cell.

[0046] (4) Interface layer impedance test: The AC impedance of three symmetrical cells was tested at 25°C, such as... Figure 4 As shown, the interface impedance of the Li|FTO-LLZTO-FTO|Li symmetric cell in Example 1 was 8.5 Ω·cm², while that of the Li|SnO2-LLZTO-SnO2|Li symmetric cell in Comparative Example 2 was 24 Ω·cm², and that of the Li|LLZTO|Li symmetric cell in Comparative Example 1 was as high as 200 Ω·cm².

[0047] (5) Critical Current Density (CCD) Test: The critical current density of three symmetrical cells was tested in constant current mode at 25 °C, such as... Figure 5 As shown, the CCD of the sample Li|FTO-LLZTO-FTO|Li obtained by fitting was 1.6 mA·cm. -2 The CCD of the comparative example 2 sample Li|SnO2-LLZTO-SnO2|Li was 0.8 mA·cm. -2 The CCD of the Li|LLZTO|Li symmetric cell in Comparative Example 1 is 0.4 mA·cm⁻¹. -2 .

[0048] (6) At 0.2 mA·cm -2 Stability cycling test at current density: 0.2 mA / cm² at 25°C. - Constant current charge-discharge was performed at a current density of 2, with a deposition capacity of 0.2 mAh cm⁻² per step. - ², the test results are as follows Figure 6 As shown, the sample Li|FTO-LLZTO-FTO|Li in Example 1 can cycle stably for more than 10,000 hours, while the CCD of the sample Li|SnO2-LLZTO-SnO2|Li in Comparative Example 2 can only cycle for less than 2,000 hours, and the symmetric cell of the sample Li|LLZTO|Li in Comparative Example 1 short-circuit after less than 120 hours of cycling.

[0049] Solid-state lithium metal battery performance testing The tantalum-doped garnet solid electrolyte and lithium metal treated by the methods described in Comparative Examples 1 and 2, respectively, were used to prepare solid lithium metal batteries by the method described in step 4 of Example 2. These batteries were denoted as Li|LLZTO|LFP (Comparative Example 1) and Li|SnO2-LLZTO|LFP (Comparative Example 2), respectively.

[0050] (1) Interface layer morphology: The sample prepared in Example 2 was cut with a focused ion beam (FIB) and observed by scanning electron microscopy. The results are as follows. Figure 7 As shown, a uniform and dense interface modification layer with a thickness of about 350 nm was formed between LLZTO and lithium metal, without cracks or pores.

[0051] (2) Full cell impedance test: The results are as follows Figure 8 As shown, the Li|FTO-LLZTO|LFP of Example 2 has an interface impedance of only 320Ω at 25℃, which is significantly lower than that of Comparative Example 2 and Comparative Example 1.

[0052] (3) Full cell cycle performance: Using the LLZTO sheet from Example 2 as the electrolyte, a full cell with lithium as the anode and LFP as the cathode was assembled on both sides. A long-term cycle test at 1C was conducted at 25 °C. The results are as follows: Figure 9 As shown, the Li|FTO-LLZTO|LFP battery retains a capacity of over 96.89% after more than 1000 cycles, indicating that the interface modification layer possesses excellent reversible lithium deposition / extraction and dendrite suppression capabilities. In contrast, the Li|LLZTO|LFP full cell sample's capacity drops sharply to 63.7 mAh g⁻¹ after only 200 cycles. -1 The capacity retention rate was only 43.39%, and the SnO2-modified Li|SnO2-LLZTO|LFP full cell also decreased to 103.5 mAh g after 600 cycles. -1 .

[0053] The above embodiments and comparative examples fully illustrate that this invention, through plasma magnetron sputtering of an FTO layer and its in-situ reaction with molten lithium, successfully constructs a gradient interface with thermodynamic interface energy differentiation characteristics on the LLZTO surface. This interface consists of a surface layer of LiF (high interface energy) and an inner layer of Li-Sn alloy (low interface energy), achieving a transformation in lithium deposition from "high-density small-nucleus vertical growth" to "low-density large-nucleus lateral growth," thereby significantly reducing interface impedance, suppressing dendrites, and improving cycle stability. Compared to schemes using only SnO2 (fluorine-free), this invention demonstrates significant improvement.

[0054] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing an interface modification layer between lithium metal and garnet solid electrolyte, characterized in that, Includes the following steps: S1. Prepare tantalum-doped garnet solid electrolyte; S2. Deposit an FTO layer on the surface of the tantalum-doped garnet solid electrolyte using plasma magnetron sputtering; S3. React the tantalum-doped garnet solid electrolyte with the FTO layer obtained in step S2 with molten lithium metal in situ to obtain an interface modification layer located between the tantalum-doped garnet solid electrolyte and the lithium metal.

2. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, In step S2, the plasma magnetron sputtering uses an FTO target with a SnO2 to SnF2 mass ratio of (90-98):(2-10), an argon sputtering atmosphere, a sputtering pressure of 0.25-2 Pa, and a sputtering time of 30-90 s.

3. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 2, characterized in that, The sputtering pressure is 1.5 Pa and the sputtering time is 60 s.

4. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, The in-situ reaction described in step S3 specifically involves heating to 200–400°C under an inert atmosphere for a reaction time of 0.5–2 min.

5. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, The in-situ reaction described in step S3 specifically involves heating to 300°C under an inert atmosphere for 1 minute.

6. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, The preparation of the tantalum-doped garnet solid electrolyte in step 1 includes: S1.1 mixing lithium source, lanthanum source, zirconium source and tantalum source in a molar ratio of 6.5:3:1.5:0.5, and adding an excess of 15wt% lithium source, ball milling, drying and sieving; S1.2 calcining at 950℃ for 6h to obtain precursor powder; S1.3 pressing the precursor powder into tablets and sintering at 1280~1320℃ for 10~60min.

7. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, The interface modification layer includes LiF and Li 17 Sn4.

8. The method for preparing the interface modification layer between lithium metal and garnet solid electrolyte according to claim 1, characterized in that, The morphological characteristics of the interface modification layer observed by in-situ atomic force microscopy are that lithium deposition exhibits sparse nucleation, lateral growth, and ultimately forms a flat and smooth morphology.

9. A solid-state lithium metal battery, characterized in that, It includes a positive electrode, a lithium metal negative electrode, and a tantalum-doped garnet solid electrolyte located between the two, wherein the tantalum-doped garnet solid electrolyte and the lithium metal negative electrode have an interface modification layer prepared by the method according to any one of claims 1 to 8.